Retreat - Kirakosyan, Arpine; Reed, Brittany; Hallaq, Tom G. (Kansas State University, 2018)
I do a national community outreach of scholars (graduate students and academics) who might feel isolated in a predominantly white institution, due to being from a traditionally under-represented group. This is a trend in Science Technology Engineering and Math fields and beyond in higher education. We usually get together 2-3 times a year, do a retreat, workshops, connect with like-minded folks, and work on our scholarship individually or collaboratively while being supported. I have opened up this opportunity to anyone from K-State and beyond, and any funds obtained after paying for costs for such events go back into coordinating our next event. I would love to coordinate a media project that would perhaps be an introduction of why such community outreach and interdisciplinary support is needed across the field.
Keywords: Kakali Bhattacharya